Fast and slide-free imaging. (December 2017) - Orringer, Daniel; Camelo-Piragua, Sandra
Optical imaging of fluorescently labelled tissue illuminated by ultraviolet light does not require microscope slides and makes for a rapid alternative to conventional histology.